Dangerousness and Expertise Redux - Slobogin, Christopher (2006)
Civil commitment, confinement under sexual predator laws, and many capital and noncapital sentences depend upon proof of a propensity toward violence. This Article discusses the current state of prediction science, in particular the advantages and disadvantages of clinical and actuarial prediction, and then analyzes how the rules of evidence should be interpreted in deciding whether opinions about propensity should be admissible. It concludes that dangerousness predictions that are not based on empirically derived probability estimates should be excluded from the courtroom unless the defense decides otherwise. This conclusion is not bottomed on the usual concern courts and commentators raise about expert prediction testimony-that the associated false-positive rates are too high. In fact, because they produce better-than-chance results, both clinical and actuarial risk assessments are, with certain caveats, sufficiently probative to meet the expertise threshold, whether that threshold is defined by Frye or Daubert. Rather, the rationale for the conclusionreached in this Article is that prediction testimony should only be inadmissible when its prejudicial impact outweighs its (admittedly weak) probative value. Clinical prediction testimony should be excluded from the government's case-in-chief under this formula, because of its relative invulnerability to adversarial testing. But the government should be able to use actuarial prediction testimony, asempirical evidence suggests that this type of testimony is likely to be taken for what it is worth. Finally, because of judges and juries' demonstrably strong predilection toward findings of dangerousness in commitment and sentencing proceedings, the defense should always be able to use both clinical and actuarial testimony to rebut the state's case